Caregivers' everyday moral reasoning predicts young children's aggressive, prosocial, and moral development: Evidence from ambulatory assessment. (12th August 2022) - Essler, Samuel; Paulus, Markus
Abstract: Developmental theories have proposed caregiver reactions, in particular caregivers' moral reasoning with their children, as crucial factors in children's developing morality. Yet, empirical evidence is scarce and mainly restricted to laboratory contexts. Here, we used the ambulatory assessment method to investigate how caregiver responses to moral transgressions longitudinally relate to children's emerging moral agency. On the first measurement point, mothers ( N = 220) reported on nine consecutive evenings on a moral transgression of their 5‐ to 46‐month‐olds', their emotional and verbal reactions, and how in turn their child reacted. Five months later, mothers reported on their child's aggressive and prosocial (helping, sharing, comforting) behavior. Our results demonstrated that (1) caregiver reasoning supported children's sharing and comforting behavior and was related to lower levels of children's aggressive behavior half a year later, that (2) caregiver reasoning reactions supported children's negative evaluations of their own transgressions while compliance‐based caregiver reactions (e.g., physical interventions, reprimands) were predictive of children's subsequent emotional distress and anger, and that (3) caregiver social conformity and reflective functioning abilities emerged as determinants of caregiver negative moral emotions. Thus, this study uses an innovative methodological approach to uncover key characteristics of caregiver moral reactions supporting the development of morality.